Students’ Response, Learning Interest, and Conceptual Understanding Ability of Two-dimensional Figures in Junior High School: A Study on the Use of Quizizz App - Syaifuddin, Mohammad; Rahmasari, Elfrida (Mosharafa: Jurnal Pendidikan Matematika, 2023)
Quizizz sebagai aplikasi evaluasi memiliki peranan penting untuk meningkatkan minat belajar dan pemahaman konsep matematika siswa. Di Indonesia, sudah terdapat beberapa guru menggunakan aplikasi tersebut, namun penggunaan secara luas masih belum optimal. Tujuan penelitian ini mendeskripsikan respons, minat belajar, dan kemampuan pemahaman konsep bangun datar siswa SMP berbantuan aplikasi Quizizz. Penelitian ini berjenis deskriptif kuantitatif. Subjek penelitian adalah 30 siswa SMP. Data diperoleh dari angket dan tes. Analisis data menggunakan teknik deskriptif kuantitatif dengan menghitung total skor respons, minat belajar, dan pemahaman konsep siswa yang dikonversi pada skala 100 dan dikategorilan sangat baik, baik, cukup, dan kurang baik. Hasil penelitian menunjukkan respons dan minat belajar siswa pada pembelajaran bangun datar menggunakan Quizizz berkategori baik. Rata-rata kemampuan pemahaman konsep bangun datar siswa sebesar 66 berkategori cukup baik. Dengan demikian, guru diharapkan menggunakan Quizizz dalam pembelajaran dan evaluasinya sehingga dapat meningkatkan minat siswa belajar dan berlatih kemampuan pemahaman konsep matematika. Quizizz as an evaluation application has an important role in increasing students' interest in learning and understanding mathematical concepts. In Indonesia, there are already several teachers using the application, but its use hasn’t been maximized. The purpose of this study was to describe the response, interest in learning, and the ability to understand the concept of two-dimensional figures for junior high school students with the help of the Quizizz application. This study was quantitative descriptive. The participants were 30 junior high school students. The data were obtained from questionnaires and tests. The data were analyzed using a quantitative descriptive technique by calculating the total response score, learning interest, and students' conceptual understanding converted on a scale of 100 and categorized as very good, good, fairly good, and poor. The results showed that the responses and students' interest in learning two-dimensional figures using Quizizz were in a good category. The average ability to understand the concept of two-dimensional shapes of 66 students was in a fairly good category. The teachers were expected to use Quizizz in their learning and evaluation so that it could increase students' interest in learning and practicing their ability to understand mathematical concepts.